Forming the surfaces on fourangle curved plan - V N Ivanov (RUDN Journal of Engineering Research, 2011)
The article concerns the questions of forming of the modified Coon's surfaces with inclined plane or space curved support lines on four angle plan. Using the inclined curved lines as support lines for construction of modified Coon's surfaces allows to receive many new forms of space constructions. There regards questions of erecting of the space lines on given curved four angle plan. There shown drawings of modified Coon's surfaces made with the help of 'MathCad' system.